Corrigendum to "Large Gliadin Peptides Detected in the Pancreas of NOD and Healthy Mice following Oral Administration" - Bruun, Susanne W; Josefsen, Knud; Tanassi, Julia T; Marek, Aleš; Pedersen, Martin H F; Sidenius, Ulrik; Haupt-Jorgensen, Martin; Antvorskov, Julie C; Larsen, Jesper; Heegaard, Niels H; Buschard, Karsten (Journal of diabetes research, 2017)
[This corrects the article DOI: 10.1155/2016/2424306.].